Money for Nothing : The Dire Straits of Medical Practice in Delhi, India - Das, Jishnu; Hammer, Jeffrey (World Bank, Washington, DC, 2012)
The quality of medical care received by patients varies for two reasons: differences in doctors' competence or differences in doctors' incentives. Using medical vignettes, the authors evaluated competence for a sample of doctors in Delhi. One month later, they observed the same doctors in their practice. The authors find three patterns in the data. First, what doctors do is less than what they know they should do-doctors operate well inside their knowledge frontier. Second, competence and effort are complementary so that doctors who know more also do more. Third, the gap between what doctors do and what they know responds to incentives: doctors in the fee-for-service private sector are closer in practice to their knowledge frontier than those in the fixed-salary public sector. Under-qualified private sector doctors, even though they know less, provide better care on average than their better-qualified counterparts in the public sector. These results indicate that to improve medical services, at least for poor people, there should be greater emphasis on changing the incentives of public providers rather than increasing provider competence through training.